1981
DOI: 10.1038/icb.1981.58
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stress on the Migration of Leucocytes Into the Peritoneal Cavity of Rats Following Injection of an Inflammatory Agent

Abstract: Summary. Although previous studies have shown ihal Ihe injection of exogenous corliccsteroids suppresses the infliimmatory response, no study has been made on the effecl on inflammation of endoeenous cortieosieroids released in response to stress, [n the present study ;i reduction was observed in the total number of leucocytes migtaling into the peritoneal cavity of stressed rats in response to the injection of an inllammalary agent. The reduction in tolal counts was due to & stress-induced reduction of both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…However, they also demonstrated that footshock stress enhanced the phagocytic activity of the neutrophils at the inflammatory site. Similar findings have also been observed in mice exposed to 18 h of restraint stress [55], in humans that have run until exhaustion [56] or that were exposed to moderate exercise (biking) [57], and in rats exposed to repeated restraint stress [58] or a shock-avoidance task [59]. Thus, it is possible that the effects of IS observed in the present experiments may reflect similar changes in phagocytic activity of polymorphonuclear immune cells.…”
Section: Discussionsupporting
confidence: 72%
“…However, they also demonstrated that footshock stress enhanced the phagocytic activity of the neutrophils at the inflammatory site. Similar findings have also been observed in mice exposed to 18 h of restraint stress [55], in humans that have run until exhaustion [56] or that were exposed to moderate exercise (biking) [57], and in rats exposed to repeated restraint stress [58] or a shock-avoidance task [59]. Thus, it is possible that the effects of IS observed in the present experiments may reflect similar changes in phagocytic activity of polymorphonuclear immune cells.…”
Section: Discussionsupporting
confidence: 72%
“…Stress reduces migration of leukocytes into the site of inflammation [32]. Moreover corticosteroids can decrease the permeability of the blood-brain barrier [331.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have shown the anti-inflammatory effects of acute stress [29][30][31] . However, many studies using animal models revealed that different types of acute stress are accompanied by a reduction in immune system activity [32,33] .…”
Section: Discussionmentioning
confidence: 99%